A parallel hashed Oct-Tree N-body algorithm - Warren, M. S.; Salmon, J. K. (Proceedings of the 1993 ACM/IEEE conference on Supercomputing, 1993)
The authors report on an efficient adaptive N-body method which we have recently designed and implemented. The algorithm computes the forces on an arbitrary distribution of bodies in a time which scales as N log N with the particle number. The accuracy of the force calculations is analytically bounded, and can be adjusted via a user defined parameter between a few percent relative accuracy, down to machine arithmetic accuracy. Instead of using pointers to indicate the topology of the tree, the authors identify each possible cell with a key. The mapping of keys into memory locations is achieved via a hash table. This allows the program to access data in an efficient manner across multiple processors. Performance of the parallel program is measured on the 512 processor Intel Touchstone Delta system. Comments on a number of wide-ranging applications which can benefit from application of this type of algorithm are included.